Comparison of the effects of long term aministration of cisapride and domperidone for the treatment of diabetic gastroparesis - Miyase BAYRAKTAR; Alper GÜRLEK; Sabri SAYINALP; Ayşe AKTAŞ; David H. Van THIEL; Aydan USMAN (Turkish Journal of Gastroenterology, 2019)
-